Enhancing Pancasila Education Outcomes: The Role of Blended Learning Models and Internet Self-Efficacy in Elementary Schools - Mujtahidin Mujtahidin; Moh. Wardi Moh. Wardi (AL-ISHLAH: Jurnal Pendidikan, 2025)
This study examines the influence of blended learning models and internet self-efficacy on student learning outcomes in Pancasila Education, motivated by persistently low achievement linked to the limited use of innovative instructional approaches. A quasi-experimental design was employed, involving 288 fourth-grade students from public and private elementary schools in Bangkalan, East Java. Participants were exposed to either blended learning or direct instruction. Data were analyzed using descriptive statistics and two-way ANOVA to assess the effects of the instructional model and internet self-efficacy on learning outcomes. The findings indicate that both instructional models significantly affected learning outcomes (F = 4.949, p = 0.027). Students with higher internet self-efficacy demonstrated significantly better performance (F = 8.815, p = 0.003). However, there was no significant interaction between the type of learning model and internet self-efficacy (F = 0.079, p = 0.779), suggesting that self-efficacy independently contributes to academic success regardless of instructional method. These results highlight the importance of internet self-efficacy in enhancing student learning outcomes. Although blended learning proved effective, its benefits did not vary based on self-efficacy levels. Blended learning can improve engagement and achievement in Pancasila Education. Educators are encouraged to adopt blended approaches and tailor instruction to student self-efficacy levels. Future research should explore these variables across other subjects and contexts.